Precipitation of greigite and pyrite induced by Thermococcales: an advantage to live in Fe‐ and S‐rich environments?. (1st February 2022) - Gorlas, A.; Mariotte, T.; Morey, L.; Truong, C.; Bernard, S.; Guigner, J.‐M.; Oberto, J.; Baudin, F.; Landrot, G.; Baya, C.; Le Pape, P.; Morin, G.; et al.
Summary: Thermococcales, a major order of archaea inhabiting the iron‐ and sulfur‐rich anaerobic parts of hydrothermal deep‐sea vents, have been shown to rapidly produce abundant quantities of pyrite FeS2 in iron–sulfur‐rich fluids at 85°C, suggesting that they may contribute to the formation of 'low temperature' FeS2 in their ecosystem. We show that this process operates in Thermococcus kodakarensis only when zero‐valent sulfur is directly available as intracellular sulfur vesicles. Whether in the presence or absence of zero‐valent sulfur, significant amounts of Fe3 S4 greigite nanocrystals are formed extracellularly. We also show that mineralization of iron sulfides induces massive cell mortality but that concomitantly with the formation of greigite and/or pyrite, a new generation of cells can grow. This phenomenon is observed for Fe concentrations of 5 mM but not higher suggesting that above a threshold in the iron pulse all cells are lysed. We hypothesize that iron sulfides precipitation on former cell materials might induce the release of nutrients in the mineralization medium further used by a fraction of surviving non‐mineralized cells allowing production of new alive cells. This suggests that biologically induced mineralization of iron‐sulfides could be part of a survival strategy employed by Thermococcales to cope with mineralizing high‐temperature hydrothermal environments.